The association between upper gastrointestinal endoscopic findings and internal radiation exposure in residents living in areas affected by the Chernobyl nuclear accident. - Yesbol Sartayev; Izumi Yamaguchi; Jumpei Takahashi; Alexander Gutevich; Naomi Hayashida (PLoS ONE, 2022)
Many people living around the Chernobyl Nuclear Power Plant (CNPP) have been exposed to 137Cs for several decades after the CNPP accident. Although half-life of 137Cs is about 30 years, some wild forest foodstuffs are contaminated by 137Cs even now. We pointed out in a previous report that low-dose internal radiation has been occasionally detected in people's body. Moreover, some doctors in local hospitals have claimed that internal exposure from contaminated foodstuffs may affect the digestive organs and possibly cause gastrointestinal (GI) diseases. Thus, we attempt to assess whether internal radiation exposure affects digestive organs or not, and the possible factors that influence digestive organs. Overall, 1,612 residents were assessed for internal 137Cs concentration using Whole-Body Counter and their digestive organs were screened with upper GI endoscopy from 2016-2018 in the Zhytomyr region, Ukraine. All participants answered to the questionnaire including their background, intake of wild forest foodstuff, intake frequency, smoking habits, and alcohol consumption. We checked the number of upper GI endoscopic diagnosis per person to assess the extent of damage to the upper digestive organs. Next, we statistically analyzed associations between this number and age, sex, level of internal exposure dose, alcohol consumption, wild forest foodstuff intake, and smoking. Consequently, we revealed that the number of GI diagnosis is significantly increased by factors such as sex, intake of wild forest foodstuff, and alcohol consumption. However, the average level of internal exposure of 137Cs and smoking did not relate to the number of GI diagnosis. Thus, the results of multiple regression revealed that alcohol consumption is independently related to the number of GI diagnosis that is most likely accompanied by the intake of wild forest foodstuff. In conclusion, the low-dose internal exposure may not affect the digestive organs of residents living around CNPP.